1997
DOI: 10.1063/1.119959
|View full text |Cite
|
Sign up to set email alerts
|

Properties of InGaN quantum-well heterostructures grown on sapphire by metalorganic chemical vapor deposition

Abstract: We report the growth and characterization of InGaN heteroepitaxial thin films and quantum-well heterostructures on (0001) sapphire substrates. The III-N heteroepitaxial layers are grown by metalorganic chemical vapor deposition on sapphire substrates using various growth conditions. A comparison of the 300 K photoluminescence (PL) spectra of the samples indicates that a higher PL intensity is measured for the quantum-well structures having an intentional n-type Si-doping concentration. Furthermore, three-, fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It has been suggested in the literature that phase separation and/or In concentration fluctuations is taking place within the InGaN layers and formation of "quantum-dot like areas" has been suggested. [4][5][6][7][8][9] Our x-ray studies showed that sub-layers with different lattice parameters and therefore, different strain and different In content are formed.…”
Section: Tem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested in the literature that phase separation and/or In concentration fluctuations is taking place within the InGaN layers and formation of "quantum-dot like areas" has been suggested. [4][5][6][7][8][9] Our x-ray studies showed that sub-layers with different lattice parameters and therefore, different strain and different In content are formed.…”
Section: Tem Resultsmentioning
confidence: 99%
“…4,6 This non-uniformity in InGaN quantum wells is thought to lead to a broadening in the spontaneous emission spectra. 7,8 Moreover, it was shown that spontaneous and gain photoluminescence spectra and Double-crystal and triple-axis x-ray diffractometry and transmission electron microscopy are used to characterize the microstructure, strain, and composition of InGaN layers grown on GaN by metalorganic chemical vapor deposition (MOCVD). Three different samples with increasing In concentration have been studied, all grown on GaN deposited on sapphire either with GaN or AlN buffer layers.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it has been established for both GaN/InGaN [4][5][6][7][8][9][10][11] and AlGaN/ GaN [12][13][14] heterostructures that doping of the active region produces a strong modification of the optical properties, namely: (i) a blue-shift of the photoluminescence (PL) peak, (ii) an enhancement of the emission intensity, (iii) a reduction of the laser threshold current, (iv) a reduction of the carrier radiative recombination lifetime, and (v) a reduction of the Stokes shift between PL peak and the photoluminescence excitation (PLE) spectra. On the other hand, free carrier screening of the polarization field has been investigated experimentally in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed knowledge of the effects of Si doping on the optical properties of these materials is crucial, especially for designing practical devices. Recently, the effects of Si doping on the optical properties of GaN epilayers [7,8], InGaN/GaN QWs [9][10][11], and GaN/AlGaN QWs [12,13] have been reported. However, the influence of Si doping on both optical properties and structural qualities in InGaN/GaN multiple quantum well (MQW) device structures is presently not well understood.…”
Section: Introductionmentioning
confidence: 99%